Ultrasmall Co@Co(OH)2 Nanoclusters Embedded in N‐Enriched Mesoporous Carbon Networks as Efficient Electrocatalysts for Water Oxidation. Issue 23 (20th November 2019) - Munir, Akhtar; ul Haq, Tanveer; Hussain, Iqtidar; Qurashi, Ahsanulhaq; Ullah, Ubaid; Iqbal, Muhammad Javed; Hussain, Irshad
Abstract: Metal nanoclusters (NCs, size ≤2 nm) are emerging materials in catalysis owing to their unique catalytic and electronic properties such as high surface/volume ratio, high redox potential, plethora of surface active sites, and dynamic behavior on a suitable support during catalysis. Herein, in situ growth of ultrasmall and robust Co@β‐Co(OH)2 NCs (≈2 nm) hosted in a honeycomb‐like 3D N‐enriched carbon network was developed for water‐oxidation catalysis with extremely small onset potential (1.44 V). Overpotentials of 220 and 270 mV were required to achieve a current density of 10 mA cm −2 and 100 mA cm −2, respectively, in alkaline medium (1 m KOH). More promisingly, at η 10 =240 mV, the prolonged oxygen evolution process (>130 h) with faradaic efficiency >95 % at a reaction rate of 22 s −1 at 1.46 V further substantiated the key role of the ultrasmall supported NCs, which outperformed the benchmark electrocatalysts (RuO2 /IrO2 ) and NCs reported so far. It is anticipated that the high redox potential of NCs with regeneratable active sites and their concerted synergistic effects with the N‐enriched porous/flexible carbon network are inherently worth considering to enhance the mass/charge transport owing to the nanoscale interfacial collaboration across the electrode/electrolyte boundary, thereby efficiently energizing the sluggish/challenging oxygen evolution process. Abstract : Ultrasmall clusters : The half‐cell oxygen evolution reaction (OER) limits the overall water‐splitting process owing its sluggish nature and slow kinetics. Here, ultrasmall (≈2 nm) and robust nanoclusters (NCs) of Co@Co(OH)2 assembled on honeycomb‐like N‐enriched porous carbon networks (HCN) are reported, which can accelerate the OER at extremely low onset potential (1.44 V) with high durability (>130 h).